The Coordination of Ethylene and Other Hormones in Primary Root Development - Qin, Hua; He, Lina; Huang, Rongfeng (Frontiers in Plant Science, 2019)
The primary root is the basic component of root systems. The primary root initiates during embryogenesis and develops shortly after germination, and it plays a key role in early seedling growth and survival. The phytohormone ethylene shows significant inhibition of the growth of primary roots. Recent findings have revealed that the inhibition of ethylene in primary root elongation is mediated via interactions with phytohormones, such as auxin, abscisic acid, gibberellin, cytokinins, jasmonic acid and brassinosteroids. Considering that Arabidopsis and rice are the model plants of dicots and monocots, as well as hormonal crosstalk in primary root growth has been extensively investigated in Arabidopsis and rice, a better understanding of the mechanisms in Arabidopsis and rice will increase potential applications in other species. Therefore, we focus our interest on the emerging studies in the research of ethylene and hormone crosstalk in primary root development in Arabidopsis and rice.